Intermediate Uveitis: Comparison between Childhood-Onset and Adult-Onset Disease. Issue 1 (January 2014) - Paroli, Maria Pia; Abicca, Irene; Sapia, Alfredo; Bruschi, Simone; Pezzi, Paola Pivetti
Purpose: To compare demographic and clinical data, systemic disease association, visual prognosis, and complications found in childhood and adult onset of intermediate uveitis (IU). Methods: Retrospective cohort study of 287 patients with IU: 122 (42.5%) children at onset (<16 years), 165 (57.5%) adults. The data were entered on a computer-based standardized data entry form for statistical analysis. Student t test was used regarding differences in means. To assess significance of differences in proportions, we used the χ 2 test, but when the population in the subgroup was ≤5 patients, we used the Fisher exact test (p<0.05 were deemed to be statistically significant and as reported were not corrected for multiple testing and so should be viewed as nominal). Results: A total of 61% of childhood-onset cases occurred in boys (44% in the adult group), while adult onset was more common in women (56% vs 39%) (p = 0.004, odds ratio [OR] 2.06). Regardless of the onset age, IU was frequently bilateral and idiopathic. The most frequent complication was cystoid macular edema (27.5%, p = 0.469, OR 0.85), which was also the most frequent cause of visual loss. Optic disc edema was more prevalent in children (15.5% vs 9.2%; p = 0.027, OR 1.81), ocular hypertension in adults (15.6% vs 7.5%, p = 0.007, OR 0.44). A total of 25 patients had non-idiopathic IU. A total of 14 patients had multiple sclerosis. Conclusions: Intermediate uveitis was mostly idiopathic and bilateral in both groups. Visual prognosis was good and it was not age-related. Childhood onset was more frequent in boys, adult onset in women. Endocrinal factors could be involved.